Pemanfaatan Teknologi IoT dan Aplikasi Android untuk Pengendalian Kadar Amonia pada Peternakan Unggas - Aditya Kristianto; Kevin Sirait; Triandes Sinaga (Yayasan Literasi Sains Indonesia, 2025)
This community service activity aims to implement an Internet of Things (IoT)–based system integrated with an Android application to monitor ammonia gas levels in poultry farms. The activity took place at Ziven Chicken Farm in Stabat, North Sumatra, which faces challenges related to ammonia accumulation from livestock waste. The methodology follows four phases: (1) initiation, involving initial observation and interviews with farm’s owner and workers concerning problems identifications and needs; (2) planning, including the design of the IoT solution and mobile application; (3) implementation, consisting of assembling the IoT device using the MQ-137 and DHT-22 sensors, integrating them with the ESP32 microcontroller, and developing the application connected to a cloud server; and (4) monitoring and control, which includes system performance monitoring, data validation, and evaluation of system use by the partner. The system provides real-time visualization of ammonia, temperature, and humidity levels through tables and graphs. Results show an upward trend of ammonia concentration, reaching 21 ppm on the third day, with humidity positively affecting ammonia levels. A notable spike occurred between 20:00 and 21:00 WIB, indicating the need for improved ventilation and cleaning routines. Overall, the system assists farmers in determining optimal maintenance schedules and supports the adoption of digital technologies in poultry farm management.